2012
DOI: 10.1002/uog.11870
|View full text |Cite
|
Sign up to set email alerts
|

P08.15: The role of uterine artery pulsatility index for prediction of outcome in pregnancies complicated by pre‐eclampsia

Abstract: Poster abstracts newborn, umbilical artery power Doppler with zero or reverse enddiastolic blood flow (blood flow class IIIa/IIIb) or changes in venous duct blood flow. We collected data about pregnancy, prenatal ultrasound examinations and result of pregnancy. Results: 20 pregnancies were included. All women underwent caesarian section. Indication was severe maternal complication, worsening of power Doppler or deterioration of the fetus. 4 children died in postnatal period, 3 have some birth defects. Mean tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However the predictive value for the subsequent development of adverse perinatal outcome does not seem to be clinically relevant. 9 In our study we observed that bilateral uterine artery pulsatility index has got maximum specificity for both major and minor adverse outcome among other uterine artery indices.…”
Section: Uterine Arterymentioning
confidence: 72%
“…However the predictive value for the subsequent development of adverse perinatal outcome does not seem to be clinically relevant. 9 In our study we observed that bilateral uterine artery pulsatility index has got maximum specificity for both major and minor adverse outcome among other uterine artery indices.…”
Section: Uterine Arterymentioning
confidence: 72%